Analisis Netnografi: Self-Disclosure Dalam Map Podcast Roblox - Diah Velina; Nuraida .; Lilis Sukmawati (CV. ITTC INDONESIA, 2026)
This study aims to determine the self-disclosure of Roblox Podcast Map members and to identify the factors that influence their self-disclosure. This phenomenon is interesting to study because virtual spaces provide opportunities for individuals to interact and disclose themselves differently compared to interactions in the real world. This study employed a qualitative approach using a descriptive-exploratory method, in which data were obtained through observation, documentation, and analysis of players within the Roblox Podcast Map. The theories used in this study were Social Penetration Theory and the Online Disinhibition Effect Theory to identify the stages of self-disclosure development and the influence of communication in virtual environments. The results showed that the self-disclosure process occurs gradually. At the initial stage of entering the Podcast Map, players are presented with podcast rooms containing different topics, allowing them to choose rooms according to their interests. Players then enter podcast rooms based on the topics they are interested in and adjust themselves to the atmosphere of the conversation. Furthermore, the stages of self-disclosure that emerge include introduction, information exchange, and response. This self-disclosure process is influenced by anonymity, the virtual social environment, positive responses, interest in the topic, and shared experiences. This indicates that the Roblox Podcast Map not only functions as part of a game but also serves as a communication medium capable of shaping virtual social interactions and encouraging individuals to be more open in expressing themselves.